2006
DOI: 10.1128/jvi.00888-06
|View full text |Cite|
|
Sign up to set email alerts
|

Population Level Analysis of Human Immunodeficiency Virus Type 1 Hypermutation and Its Relationship with APOBEC3G and vif Genetic Variation

Abstract: APOBEC3G and APOBEC3F restrict human immunodeficiency virus type 1 (HIV-1) replication in vitro through the induction of G3A hypermutation; however, the relevance of this host antiviral strategy to clinical HIV-1 is currently not known. Here, we describe a population level analysis of HIV-1 hypermutation in near-full-length clade B proviral DNA sequences (n ‫؍‬ 127). G3A hypermutation conforming to expected APOBEC3G polynucleotide sequence preferences was inferred in 9.4% (n ‫؍‬ 12) of the HIV-1 sequences, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
95
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 44 publications
(45 reference statements)
4
95
0
Order By: Relevance
“…Ultimately, the importance of understanding the cellular regulation of A3G gene expression is underscored by clinical observations that correlate elevated A3G expression with either the ability to resist HIV-1 exposure or successfully control infection (18,20,47). These novel insights into regulation of A3G expression may lay the molecular foundation for development of therapeutics aimed at exploiting and manipulating the A3G regulatory circuit allowing for modulation of A3G to protective levels in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, the importance of understanding the cellular regulation of A3G gene expression is underscored by clinical observations that correlate elevated A3G expression with either the ability to resist HIV-1 exposure or successfully control infection (18,20,47). These novel insights into regulation of A3G expression may lay the molecular foundation for development of therapeutics aimed at exploiting and manipulating the A3G regulatory circuit allowing for modulation of A3G to protective levels in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…A third possibility is genetic variation among individuals, and polymorphisms in A3G or cullin5 have been correlated with differences in the rates of disease progression . Finally, though not addressing cause versus effect, increased CD4 T-cell counts and decreased virus loads have each been correlated with the burden of hypermutated (inactivated) HIV-1 sequences (Pace et al 2006;Land et al 2008). It is worth noting, however, that not only does a good deal of controversy remain concerning the conclusions of some of these studies (Do et al 2005;Gandhi et al 2008) but also unambiguously establishing causality for these in vivo phenotypes can be expected to be challenging.…”
Section: Anti-hiv-1 Phenotypes Of Diverse Human Apobec Proteinsmentioning
confidence: 99%
“…The consensus dinucleotide target for deamination is also different with 5 0 -TC (substrate cytidine underlined) serving as the preferred site for A3F (Bishop et al 2004a;Liddament et al 2004;Wiegand et al 2004), rather than the 5 0 -CC defined for A3G ( §5). Numerous analyses of HIV-1 sequences recovered from HIV-1 infected persons reveal the frequent presence of G-to-A hypermutated viral DNA ( Fitzgibbon et al 1993;Vartanian et al 1994;Janini et al 2001;Kieffer et al 2005;Pace et al 2006;Kijak et al 2008;Land et al 2008). Further inspection of the local sequence context of such mutations reveals 5 0 -GG (plus sense sequence) as the predominant target and 5 0 -GA as the second most likely substrate.…”
Section: Anti-hiv-1 Phenotypes Of Diverse Human Apobec Proteinsmentioning
confidence: 99%
“…However, even in the presence of Vif, there is evidence of A3 deaminations inducing hypermutation of integrated proviral genomes (16)(17)(18)(19)(20)(21)(22)(23). There are two ways in which this occurs.…”
mentioning
confidence: 99%
“…More detailed analysis of the signatures revealed that A3G is most active at a 5=CCC motif, and A3D can be differentiated from A3F and A3H by examining a larger surrounding sequence 3= of the cytosine (30). Studies that sequenced integrated proviral genomes have shown that proviral DNAs contain mutations in multiple sequence contexts, suggesting that multiple A3s can mutate the same genome (16)(17)(18)(19)(20)(21)(22)(23). However, what was unable to be concluded from these studies was if the mutations induced from multiple A3s occurred in a single round of replication or multiple rounds of replication.…”
mentioning
confidence: 99%